Morphophonemics of Nisgha Plural Formation: A Step towards Proto-Tsimshian Reconstruction - Tarpent, Marie-Lucie (Kansas Working Papers in Linguistics, 1983)
To the purely descriptive linguist the Nisghal system of plural formation appears to be of great complexity. On the other hand, a generative phonological analysis of that system, carried as far as the data will allow, recovers an underlying morphological simplicity which has often been buried under a multiplicity of morphophonemic rules and obscured by reformation. The depth of reconstruction possible in some cases gives promising hints of the possibilities for further internal and comparative reconstruction of Proto-Interior Tsimshian (underlying Nisgha and Gitksan) and ultimately Proto-Tsimshian, leading eventually to a much surer foundation for the tracing of areal and genetic relationships between the Tsimshianic and other language families.